M103. PSYCHOLOGICAL ONLINE INTERVENTION FOR PSYCHOSIS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (18th May 2020) - Pardo Cebrián, Rebeca; González-Fraile, Eduardo; Sánchez-Gutiérrez, Teresa; Barbeito, Sara; Fernández-Castilla, Belén; Calvo, Ana
Abstract: Background: Although the use of technological advances in psychiatric treatment is relatively recent, the availability and sophistication of technologies are growing, research on psychological interventions for patients with psychosis has incorporated the use of various electronic applications, social networks, and other similar tools to provide new methods/routes of communication between therapists and patients. This new therapeutic approach may provide patients with personalized, flexible, and evidence-based interventions in their communities and even in their own homes. The aim of this study is reviewing the scientific literature about the use of online intervention for patients with psychosis to show the current state of online intervention and asses the effectiveness of these treatments. Methods: The review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We have identified articles from Pubmed and Medline databases. We included all randomized controlled trials designed to test the efficacy of the online intervention or web-based intervention to patients with psychosis. We excluded observational trials, non-randomised trial and protocol study. Studies with RCT design and the participants must not have more than 5 to 10 years of evolution since the diagnosis, and the papers have been published between 2010 and 2019, in English language. The researchers independently assessed the articles and the discrepancies were resolved by consensus. Results: We presented data about all randomized controlled trials of online interventions/ e-Health interventions/ App-mobile based and/or computer based intervention programs than were specifically designed for people with first episode psychosis or psychotic symptoms that had measured changes in functioning, quality of life or positive/negative symptoms. As unique treatment or as a complementary treatment with other psychological or psychopharmacology intervention. Discussion: Online psychological interventions can play an important role in the well-being of people with schizophrenia. The strengths and limitations of our systematic review and meta-analysis will be discussed.